Performance Analysis of Single Cylinder Diesel Engine with 2EHN Cetane Number Enhancer on Biodiesel - Kristofer Severiano Dinata; Steven Darmawan; Abrar Riza (Fakultas Teknik Universitas Pancasila, 2026)
Diesel engines remain a critical technology across multiple sectors, including transportation, industry, marine, and agriculture, due to their well-known benefits such as high fuel efficiency, robust durability, and superior torque output. Even as electric vehicle technology rapidly advances, diesel engines continue to be utilized in demanding applications that require reliable, high-power performance under harsh conditions. This enduring relevance stems from their higher thermal efficiency and remarkable ability to function in extreme environments. However, diesel fuel differs from petrol in its combustion characteristics, notably having a lower combustion rate. This rate is measured by the cetane number, with higher cetane values indicating better combustion quality. To optimize engine performance, especially when using lower-cetane diesel fuel, additives are often used to increase the cetane number. This study explores the effects of combining 2-ethylhexyl nitrate, a cetane number enhancer, with Pertamina’s biodiesel product, bio solar. Using a single-cylinder diesel engine and a prony brake for testing, the study found that a 1:100 ratio of CNE to fuel delivered the best results among all mixtures. This blend achieved the highest thermal efficiency at 30.23% and recorded the lowest brake specific fuel consumption at 7.78265E-05 kg/kWh.